Intelligent terminal device identification method of internet of things - Qingwang XIAO; Jinhua WANG; Yixiang ZHU (Dianxin kexue)
The correct identification of the terminal of the internet of things is an important prerequisite to establish a secure connection of the internet of things.The identification of the intelligent terminal is particularly important.The device identification method of intelligent terminals in internet of things under the existing technology was investigated.From the perspective of the security of the internet of things,the security problem that the device identification method was too simple to be easily falsified of the existing scheme was analyzed.Combining the achievements of project research in the field of internet of things and the experience of the industry,the identification method of multidimensional device feature information of IoT intelligent terminals was proposed.